Fusarium kamalianum, a new species of Fusarium from India from ornamental Chamaedorea seifrizii - Rana, Shiwali; Singh, Sanjay K. (Phytotaxa, 2024)
A novel species, Fusarium kamalianum, belonging to the Fusarium oxysporum species complex (FOSC), is established to accommodate a fungal pathogen that was isolated from infected Chamaedorea seifrizii (Bamboo palm). The identification of this pathogenic strain was determined based on the cultural features, asexual-morphs, and phylogenetic analysis based on translation elongation factor 1-alpha (tef-1α), RNA polymerase second largest subunit (rpb2), internal transcribed spacer region (ITS), 28S large subunit (LSU), and β-tubulin (tub2) sequence data. The detailed taxonomic descriptions, cultural, microscopic images, and phylogenetic trees are presented for the introduced taxon. The sequencing data of this isolate exhibited substantial distinctness from the previously discovered species of Fusarium and created a unique distinct clade. This is the first study that reports infection in Chamaedorea seifrizii plants caused by Fusarium species.